Tocilizumab as first-line therapy for steroid-refractory acute graft-versus-host-disease: analysis of a single-center experience. Issue 9 (29th July 2019) - Yucebay, Filiz; Matthews, Christina; Puto, Marcin; Li, Junan; William, Basem; Jaglowski, Samantha M.; Penza, Sam L.; Vasu, Sumithira; Benson, Don M.; Andritsos, Leslie A.; Devine, Steven M.; Efebera, Yvonne A.; et al.
Abstract: Acute graft-versus-host-disease (aGVHD) is a complication after allogeneic stem cell transplant. After the failure of treatment with high dose corticosteroids, steroid-refractory aGVHD (SR aGVHD) is associated with high rates of mortality. Tocilizumab has evidence of activity in SR aGVHD. For patients ineligible for trials, the OSU James Comprehensive Cancer Center has been utilizing tocilizumab as first-line therapy for SR aGVHD. We retrospectively report on 15 patients who received tocilizumab. aGVHD grading and responses were based on consensus criteria. Median age at transplant was 49 years. Median time to tocilizumab administration was 9 days (range, 3–16). Six patients had complete responses (40%) with a resolution of aGVHD. From the last contact, median overall survival for responders was not yet reached vs. 31 days for non-responders ( p  = .0002). Patients with skin and/or GI aGVHD demonstrated the greatest benefit. Patients with liver aGVHD did not respond. Future studies are needed to evaluate tocilizumab prior to steroid failure.